Progress of Equality in Humanities - Kumar Gautam Anand, Pramod Kumar (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Justice, a central role in the social process, is one of the fundamental human needs. The creation of people means expanding human decisions which are important for the concept of freedom. The most important factor in enhancing social welfare is human development, in which equality constitutes an essential tool. This essay seeks to discuss the meaning of freedom in various ways and to illustrate the position of open access to human development measures. Freedom has many assessment metrics, but often include democracy as a rights metric. For the analysis of the relationships of the relevant principles concise statistics were used. The results demonstrate an freedom that is capable of defending citizens from natural hazards (for example, flooding and earthquakes) and economic challenges (for example uneven distribution and low wages per capita) by the expansion of the human option and the development of sociodemocratic.